User Satisfaction of Distance Learning During the Covid-19 Pandemic: Effect of Information System Quality and Service Quality in Financial Education and Training Agency of Makassar - Azwar Azwar; Adji Suradji Muhammad; Darmanto Darmanto (Abjadia, 2022)
This study aims to determine the effect of information system quality and service quality of distance learning system on user satisfaction during the Covid-19 pandemic at the Financial Education and Training Agency of Makassar. This study uses a quantitative approach with multiple regression analysis techniques and frequency distribution. The results of the study found that the quality of the information system has a positive and significant effect on user satisfaction and the quality of system services has a positive and significant effect on user satisfaction. The two variables simultaneously have a positive and significant effect on the satisfaction of distance learning system users at the Financial Education and Training Agency of Makassar. In addition, in general the indicators of information system quality, service quality, and user satisfaction of the distance learning system at the Financial Education and Training Agency of Makassar were considered very good by the learning participants. Financial Education and Training Agency of Makassar as the technical implementer of BPPK is expected to be able to maintain the quality of the system and services provided in order to obtain the maximum of user satisfaction. When users are satisfied with the existing system, the achievement of learning outcomes is also expected to increase.